Palestina v ognju - Zupančič, Jernej (Geografski obzornik, 2025)
The Israeli-Palestinian (Jewish-Arab) conflict is one of the longest and most complex conflicts in the world. It is a struggle over territory and control of resources that has lasted for more than a century. Wars have shaped the political map and created a densely populated, defense-oriented cultural landscape. In the autumn of 2023, a war in Gaza began—the longest period of intense fighting so far— continuing the long history of tensions between Jews and Arabs.
Keywords: arabsko-izraelski spor; Bližnji vzhod; conflict areas; Gaza; Israel; Izrael; izraelsko-palestninska vojna; krizna območja; Middle East; Palestina; Palestinci; political geography; politična geografija; vojni konflikti